Komposisi dan Fungsi Vegetasi Penyusun Tiga Tipe Agroforestri (Studi Kasus Di Desa Nglanggeran, Gunungkidul, Daerah Istimewa Yogyakarta): Composition and Function of Vegetation Composing Three Types of Agroforestry (Case Study in Nglanggeran Village, Gunungkidul, Special Region of Yogyakarta) - Varanita, Selly; Putro, Gudiwidayanto Sapto; Ifah, Arini Al; Kiswanto, Yulius; Kasiyani, Achmad (HUTAN TROPIKA, 2025)
Community forests have an important role in improving the socio-economic value of rural communities. The research was aim to study the function and composition of vegetation and to determine the optimal value of three types of agroforestry commodities. The sampling method was carried out by purposive sampling. Ten plots were used to find out data, which were proportionally distributed in the three agroforestry types (early, intermediate, and advanced type) by using the nested sampling method. The result showed that the Important Value Index (IVI) of teak (Tectona grandis) in early agroforestry type had the highest value (164 %) among other perennial trees, followed by the bean group (92,73 %). In the intermediate agroforestry type, the highest IVI value (185,30%) for perennial trees was sengon (Albisia sp), followed by the food crops group was spices (95,39%). In the advanced agroforestry type, the highest IVI value (129,93%) of perennials was mahoni (Swietenia mahagoni), and the food crops group was spices (141,67%). The Nglanggeran Village people used agroforestry as a source of wood, food, plantations, animal feed, vegetables, and fruits. The optimal point of the agroforestry commodity function was in the early type up to the border of the intermediate agroforestry type area